Analysis of the Characteristics of Students' Critical Thinking Skills in Completing National Exam Questions - Nini Afriana; A Halim; Muhammad Syukri (Jurnal Penelitian Pendidikan IPA, 2021)
This research is motivated by the renewal of the learning paradigm in the 2013 curriculum which prioritizes the application of higher thinking skills, which aims to increase the potential and skills of students in the 21st century. One of the life skills that students must have is critical thinking skills, this study aims to analyze the characteristics of students' critical thinking skills in completing the HOTS type national exam. The sample of this study was 50 students of class XII MIA in SMA Negeri 1 Jaya in the academic year 2019/2020 using purposive sampling technique. The data collection techniques in this study were test and non-test and focus group discussion. The data analysis technique used was descriptive analysis, the results showed that overall the critical thinking skills of students in solving HOTS type national exam questions were still in the medium category with a percentage of 44.6. Of the 5 indicators that have been mastered well by students, namely indicators provide simple explanations of 71.8% and build basic skills of 68.7% while other indicators are still in the low category, namely indicators conclude by 32.4% provide further explanation of 15.9% and set strategy and tactics 34.5%.